Investigating the clinical, pathological and molecular profile of oncocytic adrenocortical neoplasms: a case series and literature review. Issue 1 (9th September 2021) - Fewings, Eleanor; Khoo Sert Kim, Serena; Larionov, Alexey; Marker, Alison; Giger, Olivier; Shaw, Ashley; Clark, Graeme R; Kosmoliaptsis, Vasilis; Challis, Benjamin G; Tischkowitz, Marc; Casey, Ruth T
Abstract : Background: Malignant oncocytic adrenocortical neoplasms (OANs) are rare tumours with a distinctive biological behaviour compared to conventional adrenocortical carcinoma (ACC). The current prognostic systems overestimate the malignant potential of these tumours, and guidance for surveillance and treatment strategies are lacking. Aim: To evaluate the utility of clinical, pathological and molecular markers in predicting the biological behaviour and outcomes of malignant OANs. Methods: A retrospective clinicopathological review of 10 histologically confirmed OANs was carried out. Whole exome sequencing (WES) of germline and paired tumour samples was performed for four of the ten OAN cases and compared to WES data from five cases of conventional ACC and data from The Cancer Genome Atlas. We reviewed all the cases of malignant OAN reported in the literature and compared to our case series. Results: Eight (80%) tumours were classified as malignant, one borderline and one benign (Lin–Weiss–Bisceglia criteria, LWB). The malignant OAN were larger tumours and had higher MIB index and Helsinki scores. Molecular profiling identified a pathogenic germline variant in MSH6 in an individual in the OAN group. The OAN samples had a lower mutation burden compared to the ACC samples. Somatic driver variants were identified in OAN and ACC samples including a pathogenic missense variant in CTNNB1 . Conclusion: In this study, the LWB classification demonstrated sensitivity for the differentiation of benign from malignant OAN. Molecular profiling identified dysregulation in DNA repair and Wnt signalling pathways in both OAN and ACC samples, suggesting a molecular overlap between OAN and conventional ACC.